FACTORS INFLUENCING STUDENT ACADEMIC BURNOUT SYSTEMATIC REVIEW - Nafa Aulia Rahma; Prihatsanti, Unika (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
The routine experienced by students in facing lectures causes stress which leads to emotional exhaustion, this situation is called academic burnout. This study aims to determine the factors that cause burnout in college students. This study aims to review previous studies on academic burnout in students, the review was carried out systematically by applying PRISMA guidelines. Online databases used in searches: Google Scholar, Google Scholar, Springer, Taylor & Francis, Sage, Researchgate with a defined search strategy previously. Screening was carried out by applying inclusion and exclusion criteria. The articles involved in the review (N = 5) have also gone through an assessment. The results of this study found several factors that influence academic burnout in students, including gender, anxiety, self-efficacy, the number of activities students participate in, the campus environment and the relationships or support they receive. from another individual.